Effect of signal modulated optical illumination on the Shrödinger wave function in a quantum well in a modulation doped field effect transistor and related device characteristics - Singh P.K.; Pal B.B. (My University, 2025)
The effect of signal modulated optical radiation on the Schrödinger wave function has been studied in a quantum well in a n-AlGaAs/GaAs modulation doped field effect transistor (MODFET) and related device characteristics. Partial depletion of the active region of the modulation doped field effect transistor has been considered. At the heterojunction interface two different models for the quantum well has been assumed: (1) a triangular potential well and (2) a modified triangular potential well of finite depth. From the knowledge of frequency dependent Schrödinger wave function sheet concentration of the two-dimensional electron gas, the drain-source current of the MODFET and the transfer characteristics as a function of signal frequency have been evaluated. The frequency dependent current-voltage characteristics are compared with the published theoretical results since no experimental data are available on similar studies. © 2000 American Institute of Physics.